2018
DOI: 10.1097/md.0000000000010113
|View full text |Cite
|
Sign up to set email alerts
|

Determinate factors of mental health status in Chinese medical staff

Abstract: Numerous previous studies have investigated the mental health status of medical staff in China and explored its associated determinate factors; however, scope and methods associated with these have introduced uncertainty regarding the results. The aim of this study was to perform a comprehensive examination of the mental health status of Chinese medical staff and its relative risk factors based on a cross-sectional survey.We conducted a broad area, cross-sectional, questionnaire-based survey of Chinese medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 9 publications
6
29
3
Order By: Relevance
“…They reported that the intervention was conducive to reducing social anxiety during the pandemic (1). Previous studies reported that the mental health of medical workers was in a worse state compared with the general population (28)(29)(30), which is consistent with the present results.…”
Section: Zhang Et Al Investigated the Effects Of Psychiatric Crisis supporting
confidence: 92%
“…They reported that the intervention was conducive to reducing social anxiety during the pandemic (1). Previous studies reported that the mental health of medical workers was in a worse state compared with the general population (28)(29)(30), which is consistent with the present results.…”
Section: Zhang Et Al Investigated the Effects Of Psychiatric Crisis supporting
confidence: 92%
“…We measured the anxiety level of the medical staff under the impact of COVID-19 epidemic, the results demonstrated that there was no substantial difference between experimental group and control group. However, it was not consistent with the anxiety scores of other two medical staff groups (direct contact treatment vs non-direct contact treatment) [25], and the anxiety scores of our two group were both lower than the medical staff from Heilongjiang province in China as compared with the studies conducted by Liu [26] and Zhou [27] respectively, this may be because all of our participants were military medical staff with relatively better psychological endurance and adjustment ability. Meanwhile, our experimental group working in Wuhan Huoshenshan Hospital, which was located in the epicenter of the crisis, they had better organizational support and more trust in equipment/infection control initiatives, so the anxiety level was not very high and their tenacity was more easily stimulated than the control group (T=0.308, P=0.028).…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies had suggested that the mental health status of medical staff was worse than in the general population (15,16). For example, Kerrien M et al (17) found that 27% of junior doctors were suffering from depression, while 28.7% were suffering from anxiety.…”
Section: Discussionmentioning
confidence: 99%